PENGEMBANGAN VIDEO ANIMASI UNTUK PEMBELAJARAN DESCRIPTIVE TEXT DALAM MATA PELAJARAN BAHASA INGGRIS - Dwi Juliati Ciptaningsih; Aloysius Mering; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe development of animated videos for descriptive text learning in English subjects is classified as the development of audio-visual technology based on the concept of learning technology using instructional design, namely through the planning, production, and evaluation stages. The type of research used in this research was the type of research and development or Research and Development (R&D). The animation video in this study was designed using the ADDIE model. The results showed that from the design expert's judgment, this animated video was declared "feasible". Likewise, student assessments stated that the design had a "positive" response. The animated video consisted of 4 videos, namely, an introduction video of Basic Competencies, Indicators, and Learning Objectives, a video containing pictures of historical buildings that serve as a stimulus, video explanations related to descriptive text material, and videos a matter of writing. User ratings of media profiles were declared "appropriate" to be used. From the results of the T Test, the video animation showed a significant difference before and after. The post-test score was getting better and showed that there was a strong effect of using animated videos on learning descriptive text. The amount of influence was analyzed by using the effect size. It can be concluded, the results of the effectiveness test indicated that this animated video was "feasible" to be used in descriptive text learning in English subjects.Keywords: Animated Video Development, Descriptive Text